Delay Probability Distributions of Acknowledged Csma/Ca with Finite Re-Transmissions over Fading Channels - Estela-Zamora, M (Institute of Electrical and Electronics Engineers Inc., 2024)
The delay distribution observed between the dll of a pair of neighbouring nodes in wireless mesh networks is studied. Specifically, we model the delay for unslotted csma with acknowledgments and multiple transmission retries under given channel access and block-fading statistics. This mac mechanism is used, for instance, by the IEEE 802.15.4 Standard. It has three different possible outcomes: fts (acknowledgement received), caf and ftf (no acknowledgement received, all transmission attempts used). We model these outcomes in terms of the maximum allowed number of channel access attempts, the maximum number of transmission attempts, the probability of busy channel and the frame-loss probability. All these parameters are local to each node and hence our model allows for modeling link delays from the perspective of each individual node. This lies in contrast with prior work, based mostly on Markov chain approaches, which tend to be computationally intensive, often mathematically intractable and require taking a global view over the network. We validate our results with Monte-Carlo simulations and show that the proposed model for frame transfer success and frame transfer failure are accurate in terms of the delay distribution and mean value. In the case of channel access failure, the model is less precise but can be used as an upper bound for the expected delay. © 2013 IEEE.